DEVELOPMENT OF POP-UP BOOK LEARNING MEDIA TO IMPROVE CLASS VII STUDENTS' MASTERY OF MUFRODAT MTs UINSU MEDAN LABORATORY - Sinaga, Emi Salsabila; Zulheddi, Zulheddi (Abjadia : International Journal of Education, 2024)
This research aims, 1) to describe the development of Pop-Up Book learning media to improve students' mastery of mufrodat, 2) to find out whether the development of Pop-Up Book learning media is effective in improving students' mastery of mufrodat in terms of validity, practicality and effectiveness of the media. This research is Research and Development (RD) research. This research was conducted at MTs Laboratory UINSU Medan with research subjects namely 20 students in class VII. The data analysis techniques used in this research are validity testing, practicality testing and effectiveness testing of learning media. Based on data analysis on the validity of learning media, it was obtained based on the results of media expert and material expert validation assessments, the media expert's assessment was 100% in the "very valid" category, and the material expert's assessment was 100% in the "very valid" category. The results of the data on the practicality of learning media were obtained from the results of teacher and student questionnaire assessments, the teacher questionnaire assessment results were 93% in the "very practical" category, and the student questionnaire assessment results were 93% in the "very practical" category. The results of the data on the effectiveness of learning media were obtained from student learning outcomes on pretest-posttest scores. In this way, it is known that there is a very significant increase in the N-Gain analysis with an average gain of 0.74 in the "high" category and a percentage of student learning completion of 70% in the "effective" category.